Promoting Sixth Graders’ Credibility Evaluation of Web Pages: An Intervention Study - Gonzalez-Ibanez, R (Elsevier Ltd, 2020)
This study investigated whether a teacher-led intervention program on online inquiry improved sixth graders performance in a credibility evaluation task. Students (N = 342) were divided into two conditions, an intervention group (190 students) and a control group (152 students). The intervention program (21 × 45 min lessons) was implemented during a six-week course as a part of normal schoolwork. The program included explicit teaching of online inquiry skills: searching for information (3 lessons), evaluating credibility of information (3 lessons), and synthesizing information (3 lessons). In addition, the skills taught were applied in two online inquiry projects comprising 12 lessons in total. The control group received business-as-usual teaching. Students’ performance in the credibility evaluation task was measured before and after the program by pre- and post-tests. In these tests, students evaluated three Web pages dealing with two topics (Computer Gaming or Reading on Screen) varying in their perspectives and argumentation. Students rated the credibility of each Web page and justified their ratings. Topic order was counterbalanced in both conditions. The background variables (Pre-test scores, Reading comprehension, Reading fluency, Gender, Topic order, and Test order in the pre-test) were controlled for in the multilevel negative binomial regression analysis. The results showed that the intervention program helped students better justify their credibility ratings by reference to source features but not to the argumentation or other aspects of the content compared to controls. Instructional implications of the findings are discussed. © 2020 Elsevier Ltd